'Watch my back and I watch yours': Beyond Habermas' public sphere concept in democratic and participatory dimensions of pre-colonial Shona society public spaces. (1st March 2019) - Ncube, Lyton; Tomaselli, Keyan G.
Debates on communication media and democracy including in Africa are largely anchored in the western Habermasian public sphere concept. Studies employing indigenous African communication platforms and symbols are scarce, prompting Zimbabwean philosopher Tafataona Mahoso to argue that while Africans have a philosophy, we have become 'illiterate' such that we cannot read our constructions and symbols. Thus, this article broadens discussions on participatory communication practices and democratic principles by engaging pre-colonial Zimbabwe communication and solidarity relational philosophies of Dariro and Dare (ubiquitous circle) largely located in traditional Shona societies. The philosophical democratic dimensions of these platforms are discussed in relation to Habermas' public sphere theory. We show that despite western thought generally regarding the non-West as a place of antiquarian traditions and unprocessed data, pre-colonial indigenous African communication systems were characterized by democratic participation, agency and public contest; at times beyond democratic practices and principles espoused by the Habermasian public sphere.